If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3cos(3x) + -4sin(4x) = 0 Remove parenthesis around (3x) 3cos * 3x + -4sin(4x) = 0 Reorder the terms for easier multiplication: 3 * 3cos * x + -4sin(4x) = 0 Multiply 3 * 3 9cos * x + -4sin(4x) = 0 Multiply cos * x 9cosx + -4sin(4x) = 0 Remove parenthesis around (4x) 9cosx + -4ins * 4x = 0 Reorder the terms for easier multiplication: 9cosx + -4 * 4ins * x = 0 Multiply -4 * 4 9cosx + -16ins * x = 0 Multiply ins * x 9cosx + -16insx = 0 Solving 9cosx + -16insx = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '16insx' to each side of the equation. 9cosx + -16insx + 16insx = 0 + 16insx Combine like terms: -16insx + 16insx = 0 9cosx + 0 = 0 + 16insx 9cosx = 0 + 16insx Remove the zero: 9cosx = 16insx Divide each side by '9osx'. c = 1.777777778ino-1 Simplifying c = 1.777777778ino-1
| 4y^2+6y+8=0 | | 64y^2+48+9= | | 64y^2+48+9=0 | | -3=v-7 | | 67x+x=717 | | -4+w=2 | | n=m/18 | | 3(x-3)-7x=27 | | 5x+16=-2x | | 3x+20=70 | | 56s^2-17s-3= | | 4x-18=x+5x | | 0=-9x^2+3x+5 | | 5x-17/4=-7 | | 0=9x^2+3x+5 | | 2n=111 | | -23+-8-(-4)= | | ((12x^-2)^0)/(6x^4y^-3) | | (9x)dx-(7x+18y)dy=0 | | 10-5t=3t-22 | | sin^2(4*x)*sin^2(4*x)= | | 7+30x=20x+9 | | sin^2(x)*sin^2(x)= | | x^4+2x^3-7x^2+10x+24=0 | | -x^2+11x-10=0 | | 6b-9c= | | F(n)=n+2 | | 48-5x=25x+8 | | 6X+Y=51 | | -16x=-106 | | 3(-2+4)-(8-11)= | | 49=-7x+7 |